Engagement and commitment in Eco-Campus activities of pre-service teachers: Confirmatory factor analysis - Hanifah Mahat; Nasir Nayan; Mohmadisa Hashim; Yazid Saleh; Saiyidatina Balkhis Norkhaidi; Ellyn Normelani; Yulian Firmana Arifin; Nasruddin Nasruddin; Norma Yuni Kartika; Rosalina Kumalawati (International Journal of Evaluation and Research in Education (IJERE), 2022)
This study was conducted to confirm the instrument of sustainability engagement and commitment in Eco-Campus activities of pre-service teacher. Respondents consisted of 500 pre-service teachers who were selected using stratified sampling techniques. The variables studied or the factors generated from exploratory factor analysis (EFA) of this study include knowledge, attitude, engagement, and commitment. Data were analyzed descriptively to obtain the reliability of the Cronbach's alpha value and confirmatory factor analysis (CFA) was used to obtain a four-factor solution using SPSS 22 and AMOS 20 software. The results of the analysis showed that the Cronbach's alpha value was in the high classification of more than 0.80. The results of the CFA analysis for the measurement model showed that the four-factor solution was compatible and acceptable based on the recommended fit indices (CMIN=214.073, DF=49, CMIN/DF=4.369, p=.000, GFI=.941, CFI=.971, TLI=.961, RMSEA=.082). As a result, the 36-item measuring model created was suitable for assessing sustainability participation and commitment in Eco-Campus activities, particularly among pre-service teachers in Malaysia.